Our Writing Could Be Otherwise: Reflections on Teaching Citational Politics as an Aspect of Academic Writing - Davies, Sarah R. (KULA)

(untitled) (University of Victoria Libraries, 2026)
This teaching reflection shares experiences of teaching citational politics in the context of a PhD course titled Writing as Thinking: Experimenting and Working with Writing as Knowledge Practice. It describes course content, and in particular the kinds of discussions that arose when students and teachers engaged with ideas of citational justice. Based on these experiences, I make two suggestions: first, that we should not consider citation practices (and their politics) in isolation, but rather as one aspect of the intertwined set of practices that comprise scholarly writing more widely; and second, that if we care about citational politics we should also seek to diversify the nature of what is accepted as "academic writing."